Ammonites and stratigraphy of a lower Bajocian (Middle Jurassic) section in Sierra Chacaico (Neuquen Basin, Argentina) - Dietze, Volker (2012)
A Lower Bajocian section from southern Neuquén Basin (Argentina), with 3 faunal horizons (sphaeroceroides, submicrostoma and giebeli horizons) in the Singularis and Giebeli zones, is described. The Giebeli Zone is relatively thick in contrast with the section at Paso del Espinacito. The ammonite species Chondromileia submicrostoma (Gottsche) is quite variable and consists of large specimens. For the first time well preserved and complete macroconch specimens of Emileia multiformis (Gottsche) are described. It is shown that the lithostratigraphic and biostratigraphic boundaries are not coincident in the studied section.